Kabi Jaẏadeba o Śrīgītagobinda - Mukhopādhyāẏa, Harekrshṇa, 1890- (Deʼja Pābaliśiṃ, 1977)
Critical study on the Vaishnavite verse work Gītagovinda, about the love of Krishna and Rādhā, Hindu deities, by Jayadeva, 12th century.